Visual Construction of Gender Roles in Bali Tourism Advertisement - Sulatra, I Komang; Eka Pratiwi, Desak Putu (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Visual content plays a fundamental part in our lives. When it comes to advertising, it is a compelling way to draw people’s attention. Videos and pictures tell a story a thousand times more efficiently than written words. Furthermore, it enables you telling your story using less space. Advertising has been defined as the most powerful, persuasive, and manipulative tool that firms have to control consumers all over the world. It is a form of communication that typically tries to persuade and convince potential customers to buy particular brand of products or service. Influencing people’s habits, creating false needs, distorting the values and priorities of our society with sexism and feminism, advertising has a crucial role in people’s life. Gender advertisement refers to the pictures in advertisements which describe stereotypical gender roles and displays. Gender presentations are used massively in advertisements to establish the role of one gender in relation with the other. This research aims at discovering how gender roles are portrayed as stereotypes in Bali tourism advertisement. The data was taken from Bali tourism advertisement video which published on YouTube. Observation method was used in collecting the data. The researchers used descriptive qualitative method in analyzing the data with pictorial analysis based on Goffman’s theory of gender (1979). Goffman argues that there are codes which can be used to identify gender. These codes of gender can be seen in the portrayals of men and women in advertising. In this study the researchers analyzed, described and interpreted the signs of portraying gender in Bali tourism advertisements